Exploring the stigma related experiences of family members of persons with mental illness in a selected community in the iLembe district, KwaZulu-Natal - Celenkosini T. Nxumalo; Gugu G. Mchunu (AOSIS, 2017)
Background: Stigma in mental illness is a serious social problem which has a multitude of consequences on the individual concerned, as well as his or her family. Research has shown that families of persons living with mental illnesses are often subjected to stigma by virtue of their association with such a person. The stigma of families is seen in the form of assignment of blame, social isolation and rejection. This stigma subsequently perpetuates a cycle of disability on the part of the patient and family. Purpose: To explore the stigma related experiences of family members of persons with mental illness in a selected community in the iLembe district of KwaZulu-Natal (KZN), in order to develop recommendations to help families cope with such stigma. Methods: This was a descriptive qualitative study; data was collected from a purposive sample of six family members, which resulted in data saturation. Semi-structured interview questions were used during data collection and content analysis using Creswell's (2009) method was done to analyse the data; resulting in the formation of themes and sub-themes which were supported by the participants' responses and existing literature. Results: Participants reported experiencing stigma from the community in the form of isolation, blame and exploitation, community neglect, as well as labelling and stereotyping. The majority of the participants reported using emotion-focused coping mechanisms to deal with the stigma they faced. Participants suggested that education of communities regarding the myths and facts about mental illness may help to curb the stigma faced by the family members of persons with mental illness. Conclusion: Based on the results of this study, it was recommended that a combination of coping strategies, together with the integration of public and private sector support, be used to holistically deal with family related stigma. It was found that ground level education and support to families is the key to curbing family related stigma of mental illness, local NGO's and the clinics would be instrumental in this area.